Investigating the Creativity in Marketing Strategy: The Role of Emotional Intelligence and Marketing Effectiveness - Fereshteh Mansourimoayyed,; Gohar, Fatemeh Yavari; Colabi, Amir Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
Given the global competitive environment and the rapid changes that are taking place, companies need to take steps to ensure the effectiveness of their units or departments. In this regard, companies should be able to increase the emotional intelligence of their employees, especially in the marketing and sales unit, which is one of the key units of any company, so that they can achieve the main goals and mission of the company and increase the effectiveness of their unit. The main purpose of this research is the effect of emotional intelligence on marketing effectiveness with regard to the role of creativity in the marketing strategy of dairy companies in Tehran province. The present research is descriptive-survey; its data collection method is library and field. To measure the hypotheses and achieve the research goals, we considered dairy companies in Tehran province as a statistical population and marketing managers, sales senior experts and marketing of dairy companies as the analysis unit. We calculated the sample size using Cochran's formula. We used questionnaire to collect information; we provided it individually to population members, and then analyze the data with the use of structural equation method and tested all hypotheses. The results indicate that the creativity in marketing strategy has a high impact on marketing effectiveness and the variable of self-awareness has the greatest impact on the creativity of marketing strategy.